Beneficial Effect of Scutellaria baicalensis Georgi Extract on Mercury Chloride-Induced Membrane Transport Dysfunction in Rabbit Renal Cortical Slices - Hong-Soo Kim; Choon-Ho Song (Journal of Pharmacopuncture, 2001)
This study was undertaken to determine whether Scutellaria baicalensis Georgi (SbG) extract exerts the protective effect against HgCl2-induced alterations in membrane transport function in rabbit renal cortical slices. The slices were treated with 0.1 mM HgCl2 for 60 min at . 37℃. HgCl2 caused an inhibition in PAH uptake by renal cortical slices. Such an effect was accompanied by depressed Na+ ─ K+ATPase activity and ATP depletion. SbG prevented HgCl2-induced inhibition of PAH uptake in a dose-dependent manner at the concentration ranges of 0.01-0.1%. HgCl2-induced inhibition of Na+ ─ K+-ATPase activity and ATP depletion were significantly prevented by 0.05% SbG. These results suggest that SbG prevents HgCl2-induced alterations in membrane transport function in rabbit renal cortical slices. Such protective effects of SbG may be attributed to inhibition of peroxidation of membrane lipid.